Efficient Antibacterial and Low Cytotoxic Potential of Silver Nanoparticles Produced Instantaneously Using Dimeric Gallate. Issue 48 (27th December 2018) - Kumar, Krishan; Saran, Mukesh; Yadav, Lalit; Shyamlal, Bharti Rajesh Kumar; Mathur, Manas; Bagaria, Ashima; Chaudhary, Sandeep
Abstract: This study reports the instantaneous synthesis of stable silver nanoparticles (AgNPs) at room temperature using a digallate (DG) derivative linked through hydrophilic oxyethylene spacer. The DG derivative was synthesized using standard ester coupling reaction and employed for the production of AgNPs. The Digallate acted as a very strong reducing and stabilizing agent as it reduced Ag ions in an aqueous media into Ag nanoparticles (DG‐AgNPs) instantaneously at room temperature. The DG‐AgNPs were characterized by UV/Vis, XPS, XRD, HR‐TEM, SEM, AFM, DLS and zeta potential measurements and were evaluated for their antibacterial potential against four different strains ( Escherichia coli, Staphylococcus aureus, Streptomyces griseus and Bacillus subtilis ). It demonstrated strong inhibitory activity with minimum inhibitory concentrations (MIC) ranging from 4.0‐6.0 μg/ml against all the tested bacterial strains. Optical density (OD) measurements and live/dead cell staining assay revealed significant antibacterial action of DG‐AgNPs. The MTT based cytotoxicity, cellular morphology and nuclear staining analysis of NIH 3T3 cells (fibroblasts) suggested DG‐AgNPs to be relatively safe as it did not reveal any growth inhibition for the optimized antibacterial concentrations. Concisely, relatively non‐toxic AgNPs have been produced rapidly at room temperature using dimeric gallate and suggested as effective and promising antibacterial agent for pharmaceutical applications. Abstract : The digallate (DG) molecule synthesized using gallic acid, a natural antioxidant following standard ester coupling reaction offer exciting strategy for the instantaneous and room temperature synthesis of crystalline silver nanoparticles (AgNPs) without requiring any additional reagent and without giving rise to side products. These AgNPs show effective antibacterial potential against both gram positive and negative bacteria and exhibit low cytotoxic response against normal fibroblast cells which suggest their possible use as an alternative antibacterial agent.